Marketing Strategy to Improve the Competitiveness of Lurik Woven Fabric MSMEs Centers in Klaten, Central Java - S. Suranto; Much. Djunaidi (Jurnal Ilmiah Teknik Industri, 2023)
Lurik" woven fabric is a product of the creative industry of micro, small and medium enterprises (MSMEs) in the weaving field. Lurik woven fabric is developed in six industrial centers (Pedan, Cawas, Bayat, Juwiring, Karangdawa and Delanggu sub-districts). Lurik woven fabric is a weaving craft, hand-made through non-machine looms (ATBM). The research aims to raise the potential of lurik woven fabric products so that they can be of interest to consumers so as to increase sales volume. The marketing strategy is carried out by implementing the 7P marketing mix (product, price, promotion, place, people, physical evidence, process) to increase sales volume. The data collection methods are through exploratory and survey methods, with a sample of respondents of lurik woven fabric buyers and a sample of entrepreneurs as informants, as well as the role of the Focus Group Discuccion Forum in designing marketing mix questionnaire questions and sales volume attributes. The method of data analysis through respondent preferences to determine the variable attributes of lurik fabric that respondents are interested in and path analysis of the marketing mix path to sales volume. Based on the results, it is concluded that lurik fabric products in Klaten Indonesia are of sufficient in quality, the price is relatively affordable/cheap, the promotion has not been maximized, the product is not widely known, the business actors are quite persistent and enthusiastic, the supporting physical means of sales are quite good.